Beclin1 Modulates Bone Homeostasis by Regulating Osteoclast and Chondrocyte Differentiation. (30th July 2019) - Arai, Atsushi; Kim, Sol; Goldshteyn, Vadim; Kim, Terresa; Park, No‐Hee; Wang, Cun‐Yu; Kim, Reuben H.
ABSTRACT: Autophagy (ATG), an important cellular recycling process whereby macromolecules or organelles are encapsulated by autophagosome and degraded upon merging with lysosome, has recently been shown to play an essential role in bone biology. However, the involvement of ATG in bone and bone‐related cells remains unclear. Here, we show that Beclin1, an ATG‐related protein involved in ATG initiation, plays a pivotal role in osteoclasts. ATG was activated during osteoclast differentiation in vitro. Beclin1 was enhanced and required for osteoclast differentiation. Mechanistically, we found that TRAF6‐mediated ubiquitination of Beclin1 at K117, but not ULK1‐mediated phosphorylation, is required for RANKL‐stimulated osteoclast differentiation. In vivo, mice lacking Beclin1 in CstK‐expressing cells exhibited an increased cortical bone thickness caused by impaired osteoclasts' function. Interestingly, these mice also exhibited diminished trabecular bone mass, which was associated with a defect in cartilage formation and chondrocyte differentiation. Collectively, our study highlights the functional importance of ATG in osteoclasts and chondrocytes, and identifies ATG as a potential therapeutic target for managing bone‐related diseases. © 2019 American Society for Bone and Mineral Research.